2020
DOI: 10.3390/en13226074
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Power Dilemma—Between Perception and Reality

Abstract: Motivated by the environmental challenges and the increase in energy demand, this review assesses the suitability of nuclear power production as an alternative option to using fossil fuels. First, we assess the competitiveness of nuclear power compared to other power sources considering its economic efficiency, environmental impact and implications for health, and conclude that this is a viable option to serve in addition to and as a backup to renewable sources. Second, we review previous findings in various f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A study conducted by Ningle Yu et al found that while around 70% of participants supported renewable energy development, only about 35% supported nuclear energy expansion, reciprocating the general attitude found in polls (Yu et al, 2012). To explain this finding, researchers have argued that the public's perception based on risks and benefits influences attitude toward nuclear power (Paraschiv & Mohamad, 2020;Visschers et al, 2011). Yu et al (2012) also discovered that over 80% of respondents living around the Tianwan power plant feared improper waste handling and bodily harm, two major reasons for the public's low opinion according to Jonathan Baron and Stephen Herzog (2020).…”
Section: Public Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Ningle Yu et al found that while around 70% of participants supported renewable energy development, only about 35% supported nuclear energy expansion, reciprocating the general attitude found in polls (Yu et al, 2012). To explain this finding, researchers have argued that the public's perception based on risks and benefits influences attitude toward nuclear power (Paraschiv & Mohamad, 2020;Visschers et al, 2011). Yu et al (2012) also discovered that over 80% of respondents living around the Tianwan power plant feared improper waste handling and bodily harm, two major reasons for the public's low opinion according to Jonathan Baron and Stephen Herzog (2020).…”
Section: Public Perceptionmentioning
confidence: 99%
“…Although these energy sources have great potential to address many prevalent issues with fossil fuels, the public is ambivalent. Surveys conducted by PEW Research Center (Tyson et al, 2022), World-PublicOpinion (2008), and other researchers have shown relatively positive support for renewable energy but a more nuanced opinion on nuclear energy around the world (Hagen & Pijawka, 2015;Paraschiv & Mohamad, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, oil price shocks affect supply security and are now affected by climate risk factors [6]. Lastly, diligent resource management might mitigate both energy security and energy transition issues by financing alternative energy generation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many countries in the world perceive nuclear energy as an alternative [29][30][31][32], despite its many disadvantages and difficult-to-overcome social resistance to this type of energy source in some countries, including Poland [1,31]. In discussions about nuclear energy, a radical polarization of positions can be noticed: Both opponents of nuclear energy and its supporters present one-sided views [33][34][35]. Meanwhile, nuclear energy-as indeed any large-scale energy source-has its real advantages and disadvantages, which should be taken into account in discussions about the shape of the future energy system [1,36,37].…”
Section: Introductionmentioning
confidence: 99%